PRESTASI BELAJAR SISWA HAFIDZUL QUR’AN DI KELAS VIII SMP IHYA’UL QUR’AN BENGKULU TENGAH - Imam Ahmad Amin; Muslikh Suyuthie; Lety Febriana; Erina Erina (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Univesitas Muhammadiyah Bengkulu, 2021)
Learning achievement is the teacher's assessment of the learning process and learning outcomes by producing change. These changes include knowledge, understanding, attitudes, applications, and abilities which include cognitive, affective, and psychomotor aspects of students. A student in a religious school, including a boarding school is not only being required to master general knowledge but also knowledge about religion. The purpose of this research was to determine The Students’ Achievement of Hafidzul Qur'an in Class VIII SMP Ihya'ul Qur'an Central Bengkulu. This research used a descriptive qualitative method. The results of the research show that students in class VIII SMP Ihya'ul Qur'an Central Bengkulu have learning achievement that can be seen from students' learning outcomes in the form of report card assessments. The students are not only smart in terms of memorizing Al- Qur'an but also achievement in class. The inhibiting factors for memorizing Al-Qur'an are laziness, different backgrounds of students, little time, and often easily forget. Meanwhile, the supporting factors for memorizing Al-Qur'an are the supporting from family, motivating from Ustadzah, supporting from Ustad / ustadzah, and rewards from school. Keywords: Learning Achievement, Hafidzul Qur'an.